LKSA ‘Aisyiyah Orphanage Girls’ and its role in achieving SDG 4 - Tarissa Aritsa Sabil; Hafid Adim Pradana; M. Subhan Setowara (Privietlab, 2026)
In the era of globalization, the role of global civil society is becoming increasingly important in shaping world politics, including global governance. However, how civil society can play an active role in global governance will be discussed in this study. This study aims to analyze how civil society organizations, such as the LKSA ‘Aisyiyah Orphanage Girls’, can influence the achievement of SDG 4, namely quality education. This study uses a qualitative analysis approach and quantitative data collection through interviews and direct observations, based on the concepts of global governance and global civil society. The results show that the orphanage performs two central roles as a global civil society actor: bridge and watchdog in contributing to the achievement of SDG 4. These roles collectively contribute to key SDG 4 targets, including expanding access to education, reducing educational inequality, and strengthening life skills through vocational and non-formal learning. However, the role of civil society does not eliminate the role of the state but rather forms a more complex and multi-layered governance system. This research provides an understanding of complementary actors, such as civil society, which can enhance governance practices and not simply replace international political institutions.